THE DEVELOPMENT OF WATERCOLOR PAINTING ACTIVITIES FOR UNDERGRADUATE STUDENTS BASED ON THE RESEARCH AND DEVELOPMENT PROCESS COMBINED WITH EXPERIENTIAL LEARNING CONCEPTS: A COLLABORATION BETWEEN THAI AND CHINESE ART TEACHERS - Phaetlakfa, Chakapong; Phaetlakfa, Korakot (Fine Arts Journal: Srinakharinwirot University, 2026)
Background and Objectives: Prevailing problems in the design of watercolor painting activities in higher educational institutions are characterized by teacher-centered instruction and an emphasis on imitation, which limits learners’ opportunities for self-directed, experiential learning. Consequently, students lack essential supportive learning skills, and these activities fail to accommodate learner diversity. To address these issues, this study entitled “The Development of Watercolor Painting Activities for Undergraduate Students based on The Research and Development Process Combined with Experiential Learning Concepts: A Collaboration between Thai and Chinese Art Teachers” aimed to develop watercolor painting activities using a research and development (R&D) process in conjunction with experiential learning theory. Additionally, the study sought to compare students’ watercolor painting and supportive learning skills before and after participating in the developed activities. Methods: This mixed-methods research utilized both quantitative and qualitative approaches. The purposively selected sample for activity development comprised 17 higher education watercolor instructors from Thailand, eight watercolor experts from Thailand and China, and two specialists from both countries. The experimental group consisted of 49 art education undergraduate students, selected through simple random sampling with the sample size determined using Yamane’s formula. The research was conducted across in three phases encompassing four stages: problem analysis, prototype development, efficiency verification, and implementation of the activity model. The research instruments included interview forms, practical performance tests, and assessment criteria for watercolor painting and supportive learning skills, all of which were validated by three experts. Key Findings: The findings revealed that: (1) the developed activity model comprised five components—concepts and principles, objectives, content, activity procedures, and assessment. The development process yielded a PAAR cyclical activity model with four stages: Planning, Action, Assessment, and Reflection, accompanied by three instructional units: “Human and Events,” “Human and Environment,” and “Human and Society.” (2) The implementation results demonstrated that students’ watercolor painting skills and supportive learning skills after participation were significantly higher than before at the .05 level. These results indicate that the activity model, grounded in experiential learning and research and development processes, effectively enhanced artistic skills and self-directed learning among undergraduate students. Implications of the Study: The development of watercolor painting activities based on experiential learning and a research and development process, emphasizes authentic, hands-on practice. This approach fosters continuous self-directed learning tailored to diverse student learning styles, effectively improves both watercolor painting proficiency and essential supportive learning skills. Conclusion and Future Study: The results confirm that integrating a research and development processes with experiential learning offers a highly effective approach for advancing higher education watercolor instruction by cultivating practical skills, critical thinking, and artistic appreciation. Future studies should consider adapting this model to other artistic disciplines to promote creative works that exhibit both aesthetic merit and enduring educational value.